Refractory duodenal ulcer healing and relapse: Comparison of omeprazole with Helicobacter pylori eradication - (:unkn) unknown (RAPID SCIENCE PUBLISHERS, 1996)
Objective: To investigate differences between omeprazole and Helicobacter pylori eradication in patients with duodenal ulcers refractory to H-2-receptor antagonists and to compare the recurrence rates after the two treatments. Design and methods: Forty-five patients with endoscopically proven duodenal ulcers refractory to H-2-receptor antagonists and H. pylori infection were randomly assigned to 8 weeks of treatment with omeprazole 40 mg/day or 4 weeks of treatment with colloidal bismuth subcitrate 480 mg/day plus metronidazole 750 mg/day and tetracycline 1000 mg/day from day 1 to day 14. Patients were evaluated endoscopically and clinically at the end of treatment. Patients with healed ulcers were followed up for 1 year after cessation of the treatment. Endoscopy was performed at 3 and 12 months. Results: Ulcer healing occurred in 100% (21/21) of patients on triple therapy and 70.5% (12/17) of those treated with omeprazole alone (P=0.0123). The relapse rate at the 3rd month was 11.7% (2/17) in the triple therapy group and 60% (6/10) in the omeprazole group (P = 0.0248). Of the patients followed to study endpoint (relapse or endoscopy at 12 months) three of 12 (25%) receiving triple therapy, compared to six of eight (75%) receiving omeprazole, relapsed (P = 0.0648). Conclusion: These results show that triple therapy is more effective than omeprazole in the treatment of refractory duodenal ulcers and reduces the rate of ulcer relapse.
Keywords: refractory duodenal ulcer; Helicobacter pylori; treatment; TRIPOTASSIUM DICITRATO BISMUTHATE; DOUBLE-BLIND; RESISTANT; CIMETIDINE; TRIAL; RECURRENCE; TDB